Continuity of patient care after treatment of acute myocardial infarction: Integrative review (Research, Society and Development, 2021)
Objective: To analyze the scientific production on the continuity of assistance to patients after treatment for acute myocardial infarction and the potential interventions of the disease. Methodology: this is an integrative literature review. While you search for forms made in the databases National Library of Medicine, Latin American and Caribbean Health Sciences Information System, Virtual Scientific Library Electronic Online, Web of Science and Scopus, in September 2020. Descriptors used: Continuity Patient Assistance; Myocardial infarction; Primary Health Care, with 31 articles selected in the last year. Content analysis was used. There are three categories listed: Identification of risk factors associated with complications in the treatment of acute myocardial infarction; Strategies to help reduce rates of hospital readmission after treatment for acute myocardial infarction; and Continuity of care through care and management of medication administration. Results: After the 31 items selected, there was a concern with the early identification of two precipice factors; Creation of strategies to reduce hospital readmission and outline care plans according to the international literature, mainly, not for Brazil with themes and incipients. Studies lacking evidence that emphasize the participation of nursing in the implementation of strategies that do not accompany the post-infarction patient. Conclusion: We added information to the development of strategies to reduce hospital readmission, to the application of two models for predicting risk and satisfaction factors, helping in the non-planning of illness interventions and increasing survival.